2014
DOI: 10.7566/jpsj.83.083702
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Novel Antiferromagnetic Order Intervening between Two Superconducting Phases in LaFe(As1−xPx)O: 31P-NMR Studies

Abstract: Systematic31 P-NMR studies of LaFe(As1−xPx)O compounds have revealed the emergence of a novel antiferromagnetic ordered phase (AFM-2) at 0.4≤ x ≤0.7 that intervenes between two superconductivity (SC) phases. This AFM-2 phase with Néel temperature TN= 35 K for x=0.6 is in strong contrast to the AFM order (AFM-1) at x=0 exhibiting TN of 140 K. Previous 31 P-NMR studies of LaFe(As1−xPx)(O1−yFy) have revealed that Tc reaches a maximum of 24 K for x=0.6 as a result of the marked enhancement of AFM spin fluctuations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
60
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 30 publications
9
60
6
Order By: Relevance
“…3 In the four above-mentioned IBSs (LaFeAsO 1−x F x , LaFeAs(O 1−x H x ), LaFe(As 1−x P x )O, (Ca 4 Al 2 O 6 )Fe 2 (As 1−x P x ) 2 ), the first dome is associated with an antiferromagnetic order. 54,[56][57][58] In this work, however, FeS at ambient pressure is non-magnetic above T c and we note that the normal-state resistance curve of FeS with P around 4 GPa is quite flat at low temperature, which does not show a non-Fermi liquid behavior. Therefore, it is not clear whether the first dome in FeS comes from a magnetic QCP.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…3 In the four above-mentioned IBSs (LaFeAsO 1−x F x , LaFeAs(O 1−x H x ), LaFe(As 1−x P x )O, (Ca 4 Al 2 O 6 )Fe 2 (As 1−x P x ) 2 ), the first dome is associated with an antiferromagnetic order. 54,[56][57][58] In this work, however, FeS at ambient pressure is non-magnetic above T c and we note that the normal-state resistance curve of FeS with P around 4 GPa is quite flat at low temperature, which does not show a non-Fermi liquid behavior. Therefore, it is not clear whether the first dome in FeS comes from a magnetic QCP.…”
Section: Discussioncontrasting
confidence: 47%
“…[56][57][58] In LaFe(As 1−x P x )O, the first superconducting dome appear at 0.2 ≤ x ≤ 0.4 while the second dome emerges at x > 0.7. 56,57 As for (Ca 4 Al 2 O 6 )Fe 2 (As 1−x P x ) 2 , a nodeless superconducting phase lies between 0 ≤ x ≤ 0.4 while another nodal one is around x = 1. 58 Actually, a superconducting dome in T-P or T-x phase diagram has been commonly observed in unconventional superconductors, including heavy-fermion/cuprate/organic superconductors, and IBSs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has recently been revealed that another local maximum of T c (we will call this the second T c dome) exists in the high phosphorous content regime 7,8,10 . Moreover, for the non-fluorine-doped system, the antiferromagnetic phase sandwiched by the two superconducting phases were found in the finite P doping region [9][10][11] . In order to investigate this problem theoretically, some of the authors of the present paper have recently studied the correlation between the Fe-Pn-Fe bond angle and the spin-fluctuation-mediated superconductivity 12 .…”
Section: Introductionmentioning
confidence: 98%
“…As seen in Fig. 1, the phase diagram of LaFe(As 1−x P x )-(O 1−y F y ) is very rich; in the x variation at y = 0, the superconductivity is divided into two phases by the antiferromagnetic AFM2 phase [10,11], and at x = 0, the highest T c phase (SC3) in the LaFeAsO system was reported in the H doping [12] and AFM3 with the different magnetic structure than that of AFM1 was found with further H doping [13].…”
mentioning
confidence: 98%